Interrogative Words: Types and Usage at Al-Rummani's Explanation of Sibawayh Book - Saddam Saad , Researcher. Hana; Dawud Salman, Prof. Dr. layth (Basra studies journal, 2025)
This study examines the interrogative words used by Al-Rummani in his commentary on Sibawayh’s Book. These words played a key role in presenting and organizing grammatical content. Often appearing at the beginning of sections, they served as introductions and transitions into deeper explanations. Their variety reflects Al-Rummani’s awareness of the specific nature of each grammatical issue, with each tool chosen to highlight a particular aspect. His use of interrogatives shows a deliberate effort to guide thought and stimulate reflection. The study identifies these words, clarifies their basic meanings, and analyzes their contextual functions. The findings shed light on Al-Rummani’s explanatory style and interpretive approach.